Auerbach, Madness, and the East - Khayyat, E. (2018)
Erich Auerbach's lack of interest in engaging with non-Western contexts and literatures has often led critics to identify varying degrees of Eurocentric bias in his work. This perception of bias obfuscates the depths of Auerbach's thought regarding the non-European, who does have a central place in Auerbach's overall vision, not only of philology and Western literature, but also of humanism and historical progress generally. This articles accounts for the centrality of the non-European in Auerbach's notion of realism.
Das gedruckte Heft ist als Doppelheft erschienen: "Volume 19 Numbers 7-8 November-December 2018"
Keywords: Aurbach; Realism; Comparative Literature; Conversion; Literature and religion; Orientalism